THE ANALYSIS OF FACTORS WHICH AFFECTS THE ANXIETY LEVEL OF PATIENT’S FAMILY TREATED IN INTENSIVE CARE UNIT AT GENERAL HOSPITAL OF WEST NUSA TENGGARA IN 2015 - A’an Dwi Sentana (poltekkes kemenkes mataram, 2016)
Abstract : Anxiety is an emotional reaction which appears by non-specific causes that can lead to feel worry, discomfort and feel threatened. Inadequate family mechanism to cope these feelings will create unbalanced state of the family, hence the family needs to adapt to the stress, in some families often experience a decreased of ability for adaption and it becomes the cause of anxiety, then it has an impact for health. From the interview which is conducted by researcher in Intensive Care Unit at General Hospital of West Nusa Tenggara, from 10 people, 8 other people used the mechanisms of maladaptive to cope the feeling. This would reduce the family’s support, in consequence it caused the family who was ill and treated in Intensive Care Unit will recover longer. The purpose of the study is to determine the anxiety level of patient’s familiy which is treated in Intensive Care Unit at General Hospital West Nusa Tenggara in 2015. The research used the correlation design with a cross-sectional design. The population on the study is the family of the patients which is treated in Intensive Care Unit at General Hospital West Nusa Tenggara. The sample on the study was 32 respondents, which is obtained by using accidental sampling. Data collection of anxiety level used the questionnaire HRS-A (Hamilton Rating Scale for Anxiety). The result of the study showed that the level of anxiety family includes category No Worried was 4 people (12.5%), mild category was 16 people (50.0%), the medium category was 6 people (18.8%), severe category was 4 people (12.5%) and extremely severe category was 2 people (6.3%). Chi-Square test showed there was a relationship between the anxiety level with age p = 0.003, Gender values p = 0.050, Experience values p = 0.048, knowledge values of p = 0.024 and personality values p- = 0,010. The conclusion, there are a relationship among the factors which influences the anxiety level of patient’s family. The suggestions is service providers are expected to give a counseling relates to the reduction of anxiety level of patient’s family, accompanied with the implementation of therapeutic communication methods